Impacts of integration of wind farms on voltage stability margin - Hani Attar; Mehrdad Ahmadi Kamarposhti; Ahmed Amin Ahmed Solyman (International Journal of Electrical and Computer Engineering (IJECE), 2022)
The current methods use conservative voltage based on the maximum wind speed with simultaneous occurrence in peak loading conditions to determine the maximum size of the wind farm. Wind patterns never let the wind farm on the wind farm site produce its maximum capacity during hours of heavy loading conditions. A new method is presented in this research to determine the maximum size of wind farms including voltage stability margin (VSM) and wind patterns at the wind farm site in the size of a wind farm. This plan is a method to increase the maximum size of a wind farm with a limited wind generation option under certain conditions based on VSM. The proposed method is applied to the wind farm in the IEEE 14-bus network power system. The results of the new method show that the maximum size of wind farms increases when the system operates with intermittent wind control to maintain the voltage stability.